Consider the sequence defined as

$x_1 = 1$

$x_{n+1} = \sin x_n$

I think I was able to show that the sequence $\sqrt{n} x_{n}$ converges to $\sqrt{3}$ by a tedious elementary method which I wasn't too happy about.

(I think I did this by showing that $\sqrt{\frac{3}{n+1}} < x_{n} < \sqrt{\frac{3}{n}}$, don't remember exactly)

This looks like it should be a standard problem.

Does anyone know a simple (and preferably elementary) proof for the fact that the sequence $\sqrt{n}x_{n}$ converges to $\sqrt{3}$?


Before getting into the details, let me say: The ideas I'm talking about, including this exact example, can be found in chapter 8 of Asymptotic Methods in Analysis (second edition), by N. G. de Bruijn. This is a really superb book, and I recommend it to anyone who wants to learn how to approximate quantities in "calculus-like" settings. (If you want to do approximation in combinatorial settings, I recommend Chapter 9 of Concrete Mathematics.)

Also, this isn't just about $\sin$. Let $f$ be a function with $f(0)=0$ and $0 \leq f(u) < u$ for $u$ in $(0,c]$ then the sequence $x_n:=f(f(f(\cdots f(c)\cdots)$ approaches $0$. If $f(u)=u-a u^{k+1} + O(u^{k+2})$ (with $a>0$) then $x_n \approx \alpha n^{-1/k}$ and you can prove that by the same methods here.

Having said that, the answer to your question. On $[0,1]$, we have $$\sin x=x-x^3/6+O(x^5).$$ Setting $y_n=1/x_n^2$, we have $$1/x_{n+1}^2 = x_n^{-2} \left(1-x_n^2/6+O(x_n^4) \right)^{-2} = 1/x_n^2 + 1/3 + O(x_n^2)$$ so $$y_{n+1} = y_n + 1/3 + O(y_n^{-1}).$$

We see that $$y_n = \frac{n}{3} + O\left( \sum_{k=1}^n y_k^{-1} \right)$$ and $$\frac{1}{n}y_n = \frac{1}{3} + \frac{1}{n} O\left( \sum_{k=1}^n y_k^{-1} \right)$$ Since we already know that $x_n \to 0$, we know that $y_n^{-1} \to 0$, so the average goes to zero and we get $\lim_{n \to \infty} y_n/n=1/3$. Transforming back to $\sqrt{n} x_n$ now follows by the continuity of $1/\sqrt{t}$.

  • 32
    $\begingroup$ PS This is a good example of why I find the O() notation insanely more useful than limits. $\endgroup$ Aug 24 '10 at 18:12
  • $\begingroup$ Well done! Brute force wins! This is a very straightforward proof without the need to appeal to a nested set of theorems, each of which requires proof. $\endgroup$
    – Mark Viola
    Mar 5 '15 at 19:19

This problem can be found in Kaczor, Nowak: Problems in Mathematical Analysis I, Real Numbers, Sequences and Series. I'll copy their solution here.

Problem 2.5.22, p.50, a solution is given on p.215.

Problem 2.5.22. The sequence $(a_n)$ is defined inductively as follows: $$0<a_1<\pi \qquad a_{n+1}=\sin a_n \text{ for }n\ge 1$$ Prove that $\lim\limits_{n\to\infty} \sqrt n a_n = \sqrt3$.

Solution: It is easy to see that the sequence $(a_n)$ is monotonically decreasing to zero. Moreover, an application of I'Hospital's rule gives $$\lim\limits_{x\to 0}\frac{x^2-\sin^2x}{x^2\sin^2x}=\frac13.$$ Therefore $$\lim\limits_{n\to\infty}\left(\frac1{a_{n+1}^2}-\frac1{a_n^2}\right)=\frac13$$ Now, by the result in Problem 2.3.14, $\lim\limits_{n\to\infty} na_n^2 = 3$.

Problem 2.3.14, p.38, a solution is given on p.184.

Problem 2.3.14. Prove that if $(a_n)$ is a sequence for which $$\lim\limits_{n\to\infty}(a_{n+1}-a_n)=a$$ then $$\lim\limits_{n\to\infty}\frac{a_n}n=a.$$

Solution: In Stolz theorem we set $x_{n}=a_{n+1}$ and $y_n=n$.

Formulation of Stolz theorem in this book is the following

Let $(x_n)$, $(y_n)$ be two sequences that satisfy the conditions:

  • $(y_n)$ strictly increases to $+\infty$,
  • $$\lim\limits_{n\to\infty} \frac{x_n-x_{n-1}}{y_n-y_{n-1}}=g.$$

Then $$\lim\limits_{n\to\infty} \frac{x_n}{y_n}=g.$$

For Stolz-Cesaro theorem see also this question: Stolz-Cesàro Theorem

Perhaps it is also worth mentioning that there are two equivalent forms of Stolz-Cesaro theorem: see e.g. this answer.

  • 4
    $\begingroup$ Another source: Polya-Szego, Problem and Theorems in analysis I, Spronger-Verlag, problems 173-174, p.38 $\endgroup$ May 25 '12 at 16:26
  • $\begingroup$ .........Thanks! $\endgroup$
    – Aryabhata
    May 25 '12 at 19:17
  • $\begingroup$ Now I noticed that this question also has an answer based on Stolz-Cesaro: Need help solving Recursive series. $\endgroup$ Jun 17 '12 at 6:07
  • $\begingroup$ I wish to you all the best :-) I not forgot. Thank you very much .... $\endgroup$
    – Sebastiano
    Dec 9 '20 at 22:53

If your sequence is of the form $$x_{n+1} = f(x_n)$$ with $$f(x) = x( 1 - c x^{\alpha} + \textrm{h. o. t} )$$ then notice ( e.g. ) that $$\frac{1}{f(x)^{\alpha}} = \frac{1}{x^{\alpha}} + \alpha c+ \textrm{h. o. t.}$$ and so $$\frac{1}{x_{n+1}^{\alpha}} - \frac{1}{x_n^{\alpha}} \to \alpha c$$ and with Cesaro-Stolz we get $$\frac{1}{n x_n^{\alpha} } \to \alpha c$$

In the particular case $f(x) = \sin x= x( 1 - \frac{x^2}{6} + \cdots)$, we get $$\frac{1}{n x_n^2} \to 2 \cdot \frac{1}{6} = \frac{1}{3}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.